A RARE CASE OF TENDINOUS INSERTION OF CORACOBRACHIALIS ASSOCIATED WITH VARIANT MUSCULOCUTANEOUS NERVE - Khizer H. A. Mookane; Sangeeta Muralidharan (Asociación Argentina de Anatomía Clínica, 2020)
We report a rare case of the tendinous insertion of coracobrachialis muscle which has not been reported in the literature. The insertion of the novel coraco-brachialis muscle is usually into the medial border of the humerus in a 3-5cm impression at the mid-shaft level. Contrary to this, in the present case, it was seen getting inserted as a sharp slender tendon in the middle of the medial border of the humerus.  Variable insertion of coracobrachialis muscle may be responsible for the causation of compression of surrounding structures like median nerve, musculocutaneous nerve, and brachial artery. This article aims to point out a rare case of the unusual tendinous insertion of coracobrachialis and its association with musculocutaneous nerve, providing necessary information to surgeons performing surgical reconstruction using coracobrachialis.